Pendampingan Pengembangan Pemasaran Digital Pada BUMDes Artha Jaya, Desa Yogyakarta Selatan - Lidya Ayuni Putri; Mutiasari Nur Wulan; Yuniarti Fihartini; Dwi Asri Siti Ambarwati; Dorothy RH. Pandjaitan (Penerbit Goodwood, 2022)
Purpose: The purpose of the community service done is to develop the online marketing of building materials stores owned by Artha Jaya Village-Owned Enterprises or commonly known as BUMDes Artha Jaya so that the manager of BUMDes can still increase sales during pandemic through online sales like social media Methodology/approach: The implementation of the activity used a participatory approach through a direct approach by involving BUMDes in carrying out the stages of activities consisting of preparation and implementation. In each of these activities, BUMDes and the service team carried out and compiled digital marketing of social media and e-commerce. Results/findings: The development of digital marketing in BUMDes Artha Jaya only appeared in certain types of digital marketing, namely social media marketing through the Whatsapp application and content marketing, therefore by carrying out digital marketing at BUMDes Artha Jaya accompanied by training on BUMDes administrators could assist BUMDes in promoting their business. Conclusion: BUMDes should have felt the advantage of existing marketing, because digital marketing is very efficient for businesses. Then, with the development of digital marketing, it would make the business run better.